MANAGING THE POPULATION ADMINISTRATION SYSTEM OF SOKET LAOK VILLAGE, BANGKALAN, MADURA - Liestianingsih Dwi Dayanti; Ratih Puspa; Rachmah Ida; Yuyun Wahyu Izati Surya; Titik Puji Rahayu; Nisa Kurnia Ilahiati; Angga Prawadika Aji (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Unorganized population administration information system is the major problem in village administrations, including in Soket Laok Village, Bangkalan Regency. This unorganized system has impact on poor population and village economic potential data. This evidence becomes a major obstacle to improve community welfare and creates a significant setback in attempt to distribute any kind of assistance from the higher government. Therefore, it is necessary to organize a population administration system based on simple information technology and to improve the skills of village officials in fixing the population administration system. Purpose: To manage the village population administration system using simple information technology and to improve the skills of village officials in handling the population administration system. Methods: the method used in this program was a simple application of a population administration system based on Memento's digital app, which became the main focus in subsequent training session. The training was conducted in a form of webinars through the Zoom app and simple tutorials via YouTube. Results: the result of this activity is the availability of a population data collection system using the Memento application, a simple application that can be operated by village officials with a smartphone without an internet network in accordance with the conditions of Soket Laok Village which has not been evenly reached by the internet network. Another result is the increased skills of village officials in collecting population data using the Memento application. Conclusion: In this activity, village officials can have the skills to manage the village population administration system.